Applicability of BALAD score in prognostication of hepatitis B‐related hepatocellular carcinoma. Issue 10 (October 2015) - Chan, Stephen L; Mo, Frankie; Johnson, Philip; Li, Leung; Tang, Nelson; Loong, Herbert; Chan, Anthony W H; Koh, Jane; Chan, Anthony T C; Yeo, Winnie
Abstract Background and Aims The BALAD score is developed to provide an objective determination of prognosis for hepatocellular carcinoma (HCC) by incorporating five serum markers, namely albumin, bilirubin, alpha‐fetoprotein (AFP), agglutinin‐reactive alpha‐fetoprotein (AFP‐L3), and des‐γ‐carboxy prothrombin. We aim to study the applicability of BALAD score and prognostication of the three tumor markers in hepatitis B virus‐related HCC. Methods Patients with newly diagnosed HCC were prospectively enrolled. All of the baseline characteristics and serum albumin and bilirubin level were documented at baseline. The levels of the three tumor markers (AFP, AFP‐L3, and des‐γ‐carboxy prothrombin) were determined in archival serum samples. Patients were followed up for survivals according to local practice. The prognostic performances of the three markers and BALAD score were studied in association with overall survival (OS). Results A total of 198 patients with hepatitis B‐related HCC were recruited. AFP and AFP‐L3 levels were independent prognostic factors. The number of elevated tumor markers was also predictive of worse OS. BALAD score could stratify the cohort into different patient groups with distinct median OS. The median OS of BALAD score of 0, 1, 2, 3, and 4 was not reached, 26.6, 8.3, 2.6, and 1.9 months, respectively (P < 0.0001). BALAD score could further stratify outcomes in each Barcelona Clinic Liver Cancer (BCLC) subgroup. In particular, BALAD score of 3–4 had median OS of 2.6 months only in BCLC stage C patients. Conclusion BALAD score is applicable in the population of hepatitis B virus‐related HCC. The combined use of BALAD score and BCLC staging system could help identify more suitable candidates for clinical trial.